„Witold Lutosławski. Correspondence with his Western Publishers and Managers. 1966–1994”, red. Zbigniew Skowron, t. 1–2, Kraków 2018 - Małgorzata Sieradz (Muzyka, 2022)
Recenzja książki: Witold Lutosławski. Correspondence with his Western Publishers and Managers. 1966–1994, red. Zbigniew Skowron, t. 1–2, Kraków 2018.